Rezension von: Bauer, Ernst Waldemar (Hrsg.), Unser Land Baden-Württemberg - Pastor, Egil (Württembergisch Franken, 1987)
Unser Land Baden-Württemberg. Hrsg. v. Ernst W. Bauer [u.a.]. Mit Beitr. von Ernst W. Bauer [u.a.]. Stuttgart: Theiss 1986. 335 S., Abb.